2022
DOI: 10.3390/app12178559
|View full text |Cite
|
Sign up to set email alerts
|

Performance-Based Fibre Design for Ultra-High Performance Concrete (UHPC)

Abstract: The paper presents a method to establish a performance-based fibre design of high-strength micro steel fibres for ultra-high-performance concrete (UHPC). The performance-based fibre design considers effects of fibre layout, fibre orientation, and type of loading (quasi-static and cyclic) and expands the current approach using experiences and suitability testing results. The performance-based fibre design is based on a so-called utilization rate, which is determined via pullout tests of high-strength micro stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Therefore, ultra-high-performance fibre-reinforced concrete (UHPFRC) usually requires high-strength micro steel fibres. Monotonic pull-out tests and calculations in [26] on the reference ultra-high-strength concrete with fibres showed that the fibre stresses were always smaller than the tensile strength of the fibre material. However, the results also show that fibre rupture occurs under cyclic loading.…”
Section: Fibre-reinforced Concretementioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, ultra-high-performance fibre-reinforced concrete (UHPFRC) usually requires high-strength micro steel fibres. Monotonic pull-out tests and calculations in [26] on the reference ultra-high-strength concrete with fibres showed that the fibre stresses were always smaller than the tensile strength of the fibre material. However, the results also show that fibre rupture occurs under cyclic loading.…”
Section: Fibre-reinforced Concretementioning
confidence: 95%
“…The demonstrators used are notched beams with a span of 3.0 m, a height of 30 cm and a width of 15 cm. The concrete mixture and fibre type remained the same as in [26]. Figure 10 shows the evolution of the CMOD (crack mouth opening displacement) depending on the load cycles.…”
Section: Fibre-reinforced Concretementioning
confidence: 99%
See 1 more Smart Citation